Analysis of the implementation of projects for the development of sports infrastructure in the Russian Federation - Stepyko, D. G.; Aleksandrov, D. S.; Gracheva, D. V.; Javid Allahverdi Ogly Farzaliev (Theory and Practice of Physical Culture, 2017)
Subject to the study were some aspects of the sport infrastructure development in the Russian Federation with an emphasis on the most efficient public-private partnership (PPP) projects implementation and relevant operational arrangements at different levels.